The Relationship Between Rhythmic Gymnastics And Physical Fitness of Mentally Retarded Children - Rosidin, Darmeswara (Sains Global Institut, Indonesia, 2024)
This study aims to explore the relationship between rhythmic gymnastics and physical fitness in mentally retarded children. This research method uses qualitative data collection involving observation of participants during the rhythmic exercise program and measuring physical fitness levels using relevant tests. The data collection process in this research was carried out through observation, interviews, and documentation studies at SLB Pembina Ci, Alaka Sumedang. The results of the research show that rhythmic gymnastics has the potential to make a positive contribution to improving the physical fitness of mentally retarded children. Implications for the development of rhythmic exercise programs as part of physical education and rehabilitation for children with intellectual disabilities are discussed.